(untitled) (Journal of Teaching Innovation and Reform, 2026)
This article reports part of a bigger scale ‘Design and Development Research’ (DDR) Study aimed at examining preliminary changes in primary school students’ higher-order thinking and dance learning motivation following the implementation of Unit 1 of a theory-informed creative dance module. During Stage 2 of DDR, a quantitative one-group pre-test/post-test design was employed with 24 female primary school students from an extracurricular dance institution in China over three weeks (9 instructional hours). The intervention involved Unit 1 only as part of a larger DDR as aforementioned. Two instruments were used including a modified Fluid Intelligence Test (FIT), designed to assess higher-order thinking in movement-based contexts through critical and creative thinking, and an adapted Motivation Towards Dance Learning Survey (MTDLS). Both instruments underwent two rounds of expert validation prior to use. The findings showed positive change in both outcomes. The mean motivation score increased from 3.12 to 3.85, while the mean overall FIT score rose from 64.50 to 73.42. Improvements were also found in both critical and creative thinking sub-scores.